a moving body of water ~ Architectures of Marine Protected Areas around Iceland - Sigrún Perla Gísladóttir 1996- (2024)
This master thesis, within Architectures of Care, draws out and proposes a network of Marine Protected Areas around Iceland that fulfil the global goal of at least 30% conservation by 2030 (Target 3, Kunming-Montréal Global Biodiversity Framework, United Nations Convention on Biological Diversity). It is a creative contribution to the call for the transformative change needed to manage the ongoing planetary crisis. About 25% of Iceland’s 103.000 km2 terrestrial area is protected by law already. However, only 0.07% of its 764.000 km2 seascape is. Hence, an area more than twice the size of the island itself needs to be protected within the next six years—but how? This thesis aims to shed light on how architects as spatial thinkers can work on the road ahead. The author embraces "ocean as a method" in her ways of reading the sea as an architectural space, departing from linear and optimised work processes, and makes use of oceanographic data as well as bodily explorations. The author’s love for the sea is the primus motor and solutions are drawn with cod, corals, currents, and a diverse group of human stakeholders.